The ring two [videorecording (DVD)] - Nakata, Hideo, 1961-; Parkes, Walter F.; MacDonald, Laurie; Kruger, Ehren, 1972-; Watts, Naomi, 1968-; Baker, Simon, 1969-; Dorfman, David, 1993-; Perkins, Elizabeth, 1960-; Spacek, Sissy; Cole, Gary, 1956-; Merriman, Ryan; VanCamp, Emily, 1986-; et al. (DreamWorks Home Entertainment, 2005)
Six months after the frightening rampage and the cursed videotape that left so much death and terror, Rachel and her son start a new life in a small Oregon town. But when a crime scene includes an unmarked tape, she knows the violence has not ended.